(3EYdGe GdfHjg HeG RGO Ydi GdefgGL ef GdMGhj hGdHgLI hGdJfHjgs - (3CHj HcQ Hf hdj GdOjf Hf bGVj YLdhf GdTGaYj, Jbj GdOjf,J (B928 (3g` s ((3CMeO Hf eMeO GdMSGei GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO , agPG JYdjb dWja CLeY ajg Ef TGA Gddg JYGdi eG ai GdJfHjg hGdMGhi hGdHgLI eeG dG jhLO ef GdefgGL s
(3BNQgG (B:s
(3hGdYbHGJ ai GdhdG ShjI gPG JeGe GdHgLI GdhQOjI Je GdcJGH hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eMeO YHO Gddg Bd YHO GdbGOQ GdCfUGQ GdNGUI HGdeHQR (B/ (3GdCMSGAs
Keywords: (3Gdabg GdTGaYjs